Statistical analysis of wind energy potential on the basis of the Weibull and Rayleigh distributions for Agin-Elazig, Turkey - Akpinar, EK; Akpinar, S (Sage Publications Ltd, 2004)
In the present study, the wind energy potential of the region is statistically analysed on the basis of 5 year measured hourly time series wind speed data. The probability density distributions are derived from time series data, and distributional parameters are identified. Two probability density functions are fitted to the measured probability distributions on a yearly basis. The wind energy potential of the location is studied on the basis of the Weibull and the Rayleigh models.
Keywords: Weibull distribution; Weibull parameter; wind data; wind energy